Religious education in Costa Rica: Contributions from Interculturality - Méndez Méndez, Jose Mario (2021)
In Costa Rica there is a lack of solid reflection on the curricular status of religious education. In a constitutionally multicultural and multiethnic country like this, it becomes necessary to assume the task of clarifying the specific contribution of religious education in the whole of the national educational proposal. This task involves dialogues and searches around topics like objectives, the “object of study”, methodological criteria, thematic areas to emphasize, the teacher profile, the criteria for learning evaluation and for dialogue with other curricular components of the national educational system. This work seeks to offer some clues that, along with other contributions, can contribute to the curricular rethinking of Costa Rican religious education from an intercultural perspective.